The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1016/j.annonc.2020.08.1242
|View full text |Cite
|
Sign up to set email alerts
|

1119P Targeted treatment and immunotherapy in older patients with advanced melanoma: A single institution real-life experience

Abstract: Our multicenter retrospective analysis included 499 patients treated with anti-PD-1 agents (nivolumab or pembrolizumab) between 2017 and 2019. 208 patients were aged <65 years, 218 patients were aged 65-79 years, and 73 patients were aged 80-100 years. We analysed the efficacy and toxicity of anti-PD-1 therapy at the age of 80-100 years compared to the age of 65-79 years and to <65 years. Baseline parameters, response rate (overall response rate -ORR), best response, progression-free survival (PFS), melanoma-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…18 19 Results from the phase I/II ILLUMINATE-204 trial demonstrated the safety and activity of intratumoral IMO-2125, also named tilsotolimod, in combination with systemic ICI ipilimumab in patients with anti-PD1 refractory advanced melanoma. 20 Interestingly, the antitumor activity was observed in both injected (enestic) and noninjected (anenestic) lesions (NCT02644967).…”
Section: Open Accessmentioning
confidence: 99%
“…18 19 Results from the phase I/II ILLUMINATE-204 trial demonstrated the safety and activity of intratumoral IMO-2125, also named tilsotolimod, in combination with systemic ICI ipilimumab in patients with anti-PD1 refractory advanced melanoma. 20 Interestingly, the antitumor activity was observed in both injected (enestic) and noninjected (anenestic) lesions (NCT02644967).…”
Section: Open Accessmentioning
confidence: 99%